Medical exercise therapy alone versus arthroscopic partial meniscectomy followed by medical exercise therapy for degenerative meniscal tear: a systematic review and meta-analysis of randomized controlled trials - Jianxiong Ma; Hengting Chen; Aifeng Liu; Yuhong Cui; Xinlong Ma (Journal of Orthopaedic Surgery and Research, 2020)
Abstract Objective To explore if medical exercise therapy (MET) alone is comparable to arthroscopic partial meniscectomy (APM) followed by MET for knee pain, activity level, and physical function in middle-aged patients with degenerative meniscal tear (DMT) by a systematic review and meta-analysis of randomized controlled trials (RCTs). Method A systematic search of electronic databases (PubMed, the Cochrane Library, Embase, and Web of Science) was conducted to retrieve RCTs comparing MET+APM with MET alone for DMT. Risk of bias of the studies was evaluated. Outcomes assessed were pain relief, physical function, and activity level. Results A total of 6 RCTs containing 879 patients were included. After pooling the data of 5 researches, we found small significant differences support the APM + MET group for pain control assessed by Knee injury and Osteoarthritis Outcome Score (KOOS) at 2 to 3 months (p = 0.004) and at 6 months (p = 0.04). And there were statistically improvements in APM + MET at 6 months compared with MET alone when changing measurement to visual analog scale (VAS) (p = 0.0003). Our analysis also found small significant differences favor the APM followed by MET group for physical function both at 2 to 3 months (p = 0.01, KOOS and Western Ontario and McMaster Universities Osteoarthritis Index, WOMAC; and P = 0.40, Lysholm Knee Scoring Scale) and at 6 months (p = 0.01, KOOS and WOMAC). Conclusion We found favorable results of APM + MET up to 6 months for pain control and physical function. However, there were no differences at longer follow-up. The clinical applicability of APM + MET compared with MET should be interpreted carefully, and the potential of MET to treat DMT should be valued.